Pengaruh Media Pembelajaran Daring dan Minat Belajar Terhadap Hasil Belajar Matematika Siswa Kelas V SD Negeri 03 Manado - Silvia Christiana Banobe; Fientje J. Oentoe; Agnes M. Goni; Richard D.H Pangkey; Risal M. Merentek (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to obtain the results of analysis and interpretation of online learning using zoom cloud meetings which affect the mathematics learning outcomes of fifth grade elementary school students, student interest in learning affects mathematics learning outcomes of fifth grade elementary school students, and online learning using zoom cloud meetings and interest student learning affects the mathematics learning outcomes of fifth grade elementary school students. This research is a quantitative approach research using a descriptive survey method. The instrument used in this study was a closed questionnaire. Descriptive analysis of this study was used to describe the creativity of teachers and students' learning motivation on the learning outcomes of class V Elementary School 03 Manado. Descriptive statistics include the calculation of the mode, median, mean, and standard deviation, with the prerequisite test for normality test and linearity test. In this study, data analysis used simple regression statistical tests and multiple regression. 1) The results of the first hypothesis test which stated that there was a significant influence of online learning media on the mathematics learning outcomes of students in class V, State Elementary School 03 Manado. 2) The results of the hypothesis test II which stated that there was a significant effect of student interest in learning on mathematics learning outcomes in class V Elementary School 03 Manado, and based on the results of the analysis of hypothesis III data through SPSS with a significance level of Fcount = 8.886 > Ftable 3.22 with a significance level of 0.000 and 0.001 < 0.05, so from the results of this data analysis, it can be concluded that the multiple regression model has a significant effect jointly between online learning media and students' interest in learning on students' mathematics learning outcomes.